Phenolic screening and anticancer potential of various wild savory extracts - Şi̇mşek Sezer, Ela Nur (Emirates Journal of Food and Agriculture, 2023)
Cancer is one of the leading causes of death in our age. In addition to the treatments used in cancer, plants are frequently used in complementary or alternative approaches. Plants of the genus Satureja are used world wide for various purposes, primarily as complementary therapies. For this purpose, in this study, the antioxidant potential and phenolic content of the Satureja cuneifolia plant, which is frequently consumed as a spice and tea among the public, and its cytotoxic and apoptosis-inducing effects on cancer cells were tried to be revealed. The cytotoxic effect of the extracts prepared with three different solvents (methanol, ethanol and water) was determined by the MTT test in colorectal cancer (DLD1) and promyelocytic leukaemia cell lines (HL60). Then the expression levels of five apoptotic gene regions (apaf-1, bax, bcl2, card4, casp3 and tp53) were evaluated with Real-Time PCR. The antioxidant potential was determined via the DPPH test, and HPLC was used to screen for phenolic substances. As a result, it was determined that the extracts have cytotoxic effects and have a variable but positive effect on pro-apoptotic gene expressions. When the antioxidant potential was evaluated, it was determined that the methanolic extract had a more radical scavenging effect (IC50: 105.02±0.034 µg/ml). In conclusion, the cytotoxic and apoptosis-inducing potentials of the extracts obtained from the S. cuneifolia plant were revealed for the first time upon DLD1 and HL60 cell lines in this study. This study is a pioneer for future studies in cancer therapy. Keywords: Apoptosis; qRT-PCR; Spice; Turkey; Wild savory